Facing South China Sea Dispute: Where Is Asean Single Voice? - Naeli Fitria (Publikasi Indonesia, 2023)
South China Sea disputes has become intense in challenging regional stability in Southeast Asia. The strategic location of rich natural resources, for instance, oil and gas has triggered China and other Claimant States in Southeast Asia in exercising their capability mainly in military power to secure their claimed area. China stretched its “Nine-Dash Line” and created an artificial island namely Spartly Island. To date, this unresolved disputed questioning the role of Association of Southeast Asian Nations (ASEAN) as the leader of regional organisation in dealing with this conflict. The disputes mechanisms have been exercised by ASEAN, for instance, Treaty of Amity and Cooperation (TAC) through ASEAN Regional Forum (ARF) as well as produced guidance in facing China through Declaration of Conduct (DOC) and Code of Conduct (COC). However, the progress apparently remain insignificant in achieving agreement. This paper examines ASEAN’s leadership in bridging the dispute through assessing the effectiveness of its dispute mechanisms through Confident Building Measures (CBM) as a diplomatic strategy in reaching one single voice in facing China.